Methane emissions and estimates of ruminal fermentation parameters in beef cattle fed different dietary concentrate levels - Pedreira,Márcio dos Santos (2013)
Using sorghum silage, the effect of roughage/concentrate ratios was evaluated on nutrient intake, digestibility, ruminal parameters and methane production by beef cattle. Three treatments (0, 30 and 60% of concentrate in DM of the diet) were distributed in three Latin squares, with nine animals and three periods. Dry matter intake increased as the grain concentration in diet increased; pH showed opposite behavior. Methane emissions were lower for animals fed the diet exclusively with sorghum silage as compared with those fed 30% of concentrate, but was similar to that of animals receiving 60% of concentrate. Losses of ingested gross energy as methane were reduced by 33% when grain concentration was increased in the diet. Concentrations of propionic and butyric acids were greater in diets with grain concentrate; acetic acid concentration was not affected. Concentrate in diet increases available energy for the metabolism, measured by lower losses of ingested gross energy as ruminal methane.